Comparison of Fibroblast and Vascular Cell Adhesion to Nano-Structured Poly(lactic-co-glycolic acid) Films - D. C. Miller; R. J. Vance; A. Thapa; T. J. Webster; K. M. Haberstroh (Applied Bionics and Biomechanics)
The success of small diameter vascular grafts may be attributed to the ability to accurately mimic the nano-structured topography of extra-cellular matrix components of natural vascular tissue. Using this knowledge, the goal of the present study was to develop synthetic biomaterials that promote vascular cell adhesion and growth, while subsequently limiting fibrous tissue formation. For this purpose, poly(lactic-co-glycolic acid) (PLGA) with increased nanometer surface roughness was created by treating the surfaces of conventional PLGA with NaOH. Cell experiments on these surfaces indicated that nano-structured PLGA enhanced vascular smooth muscle cell adhesion and growth, while decreasing endothelial cell and fibroblast adhesion and growth, compared to their conventional counterparts. These favorable results were attributed to the selective adsorption of vitronectin. In combination, results of the present in vitro study provided evidence that nano-structured surface features have the potential to significantly improve the efficacy of small diameter vascular implants.